El impuesto a la renta y el desarrollo del capital humano en el Perú - Zavaleta Chimbor, David Moisés (2013)
This study tries to find regularities on empirical facts that demonstrate the intervention to achieve competitiveness, with the main axis and Human Capital as an instrument the income tax by allowing within the structure of the latter deduction and / or give a credit for continuous learning. Research on the assumption that the incentives granted by the State from the application are more efficient than those granted from the offer. The income tax is only one of the tools that we have to encourage the demand side. In this sense, our investigation of the following questions What is the relationship between incentives in the income tax for continuous learning of individuals and human capital development, in a competitive and changing? How to measure the relationship between income tax and human capital development? How efficiently can finance in developing human capital?, From Popperian methodology has tested the following hypothesis: If for every object X, if X is a country that has the ability to have their income tax incentives for continuous learning of individuals, then, in a competitive and changing X has developed its human capital. He is referring to Peru but has also been tested in countries like Argentina, Costa Rica, Chile and Mexico, these were chosen through a non-probability sampling. Being that those countries that encourage continuous learning of individuals from the income tax achieve greater development of human capital.